The American Sign Language Handshape Dictionary - Tennant, Richard A. (Book collections on Project MUSE., 2010)
This reference complements other American Sign Language (ASL) dictionaries by organizing signs by handshape rather than alphabetically by English word order. In so doing, it acts best as a recognition tool for the ASL learner, leading the user quickly to specific signs without having first to refer to an English-equivalent word. Multiple meanings of a single sign also allow deaf people to increase their English vocabulary. Like other ASL dictionaries, introductory material includes a brief synopsis of the history of sign language, the meaning and importance of the five parameters of a sign (handshape, orientation, location, movement, and nonmanual signals), grammatical rules, sign language variations (dialects), and finger-spelling principles.